Poverty and intervention : Guyana - Thomas, Clive Y. ([s.n.] [S.l.], 1995)
Describes the current poverty situation in Guyana and raises a few analytical issues pertaining to the conceptualization and application of poverty studies in that country. Examines the effectiveness of various poverty alleviation programmes such as SIMAP. Includes an appendix on the community based rehabilitation programme in Guyana.